BUSINESS PLAN AS A SOURCE OF INFORMATION FOR MAKING BUSINESS DECISIONS - Boškov, Veronika (International Journal of Economic Practice and Policy, 2017)
For the successful development and business support needed to inform all interested parties about the structure of the transaction, future policies, the resources we need to realize, the effects of which we plan to achieve and of course financial effects that will follow from that job. The business plan is important precondition for starting any activities. Modern business conditons are characterized by intensive changes in the market, strong competition and increasingly demanding customers. Modern business involves meticulously market research and the possibility of profitable use of capital, which is achieved through the simulation of a business plan. It could be said that a business plan is a map of activities in developing business ideas with all the necessary activities and resources that have been tested and tested/checked first on paper. The business plan does not guarantee the company success, but is definitely a secure way to increase the likelihood of success and that through the relevant, understandable and accurate information present a set of projected activities whose results will be interested by all stakeholders to actively achieve the set goals.